The effects of modifying the distance of the penalty shot in water polo - Argudo, F. M.; Ruiz-Barquin, R.; Borges, P. J. (Journal of Human Kinetics, 2016)
The aim of this study was to determine the effects of changing the distance of the penalty shot in water polo from 4 to 5 m. While a shorter distance made the penalty shot more effective, it also reduced the use of this sanction. A total of 192 matches played in the 2003 and 2007 Water Polo World Championships were recorded. The sample included 278 penalty shots in both tournaments. Notational analysis using a longitudinal correlational and descriptive design was employed to determine whether a longer distance increased the number of sanctioned penalties (81 vs 197) and caused a non-significant decrease in scoring efficiency (7.4%) with significant differences in the relationship between the area and the type of a shot, with less centre and power shots (14.8% vs 7.1%) observed and predominance of bounce shots to the right of the goal posts. The rule change prompted more penalties, produced changes in shot direction as well as the type of a shot, and yielded a decrement of 7.4% in scoring efficiency.